Formation of tubular conduction channel in a SiGe(P)/Si core/shell nanowire heterostructure - Wang, Xuejing (2023)
Realizing a tubular conduction channel within a one-dimensional core-shell nanowire (NW) enables better understanding of quantum phenomena and exploration of electronic device applications. Herein, we report the growth of a SiGe(P)/Si core/shell NW heterostructure using a chemical vapor deposition coupled with vapor-liquid-solid growth mechanism. The entire NW heterostructure behaves as a p-type semiconductor, which demonstrates that the high-density carriers are confined within the 4 nm-thick Si shell and form a tubular conduction channel. These findings are confirmed by both calculations and the gate-dependent current-voltage (Id-Vg) characteristics. Atomic resolution microscopic analyses suggest a coherent epitaxial core/shell interface where strain is released by forming dislocations along the axial direction of the NW heterostructure. Additional surface passivation achieved via growing a SiGe(P)/Si/SiGe core/multishell NW heterostructure suggests potential strategies to enhance the tubular carrier density, which could be further modified by improving multishell crystallinity and structural design.